Flipping the classroom: Old ideas, new technologies. (September 2018) - Becker, Ralf; Birdi, Alvin
Abstract: The technique of classroom flipping has started to make an impact on the teaching of economics. An important element of classroom flipping is that elements of active learning (e.g. games, experiments and polling) are brought into the classroom setting and that content delivery is moved (at least partially) from the classroom to the virtual learning environment. This paper discusses the developments that have prepared the ground for the increasing uptake of classroom flipping, namely technical innovations and a better appreciation of how students learn. In our view the flipped classroom approach has significant promise beyond the already existing implementations, mostly by enthusiastic teaching staff. As many of the technical challenges have been solved it is now the willingness, the availability of time, and the recognition and reward of any effort to change the delivery approach that will prove to be the most significant hurdles for further adoptions.